APPLICATION OF SHAKER EXERCISE TECHNIQUE IN OVERCOMING SWALLOWING PROBLEMS IN ISCHEMIC STROKE PATIENTS: A SINGLE CASE STUDY - Saputra, Dwi Candra Ari; Pamungkas, Indra Gilang; Dewi, Aliana (Klabat Journal of Nursing, 2025)
Stroke is a clinical sign characterized by focal or global neurological deficits that may worsen and persist for 24 hours or more, potentially resulting in death. One of the symptoms experienced by stroke patients is difficulty swallowing (dysphagia). Patients with positive dysphagia are at significantly increased risk of aspiration and pneumonia. One of the independent nursing interventions for managing swallowing disorders is swallowing training using the Shaker Exercise technique. This case study aims to determine whether the Shaker Exercise technique can help improve swallowing ability in ischemic stroke patients. This study used a single case study of a patient suffering from Ischemic Stroke. This involves performing 1 intervention called the Shaker Exercise Technique. The intervention was carried out twice a day for 15–20 minutes over 5 days. The intervention was evaluated using the Royal Adelaide Prognostic Index for Dysphagic Stroke. The implementation of the Shaker Exercise showed that the patient was able to swallow after 5 days of intervention. The Royal Adelaide Prognostic Index for Dysphagic Stroke score before the intervention was 71, and after the intervention, it increased to 92, allowing the patient to swallow normally and enabling the removal of the Nasogastric Tube. Swallowing exercises using the Shaker technique can improve swallowing function in patients with positive dysphagia and are therefore recommended as a structured intervention for stroke patients experiencing swallowing disorders.